Expressive Writing untuk Meningkatkan Self-Disclosure Generasi Milenial Pengguna Sosial Media Instagram - Wahyu Eka Febriliyani; Djudiyah Djudiyah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The development of communication technology today has changed the behavior of individuals in interacting. Social media has become a means for individuals to express themselves and perform self-disclosure. This study aims to find out how expressive writing can increase self-disclosure in millennial Instagram social media users. The research method uses a qualitative approach by conducting in-depth interviews with participants. The results showed that expressive writing can facilitate individuals to express themselves and increase self-disclosure on Instagram social media users. Through expressive writing, individuals can express their feelings, thoughts, and experiences freely without any restrictions. This encourages deeper self-disclosure in millennial Instagram users. The implication of this study is the importance of using expressive writing to facilitate the self-disclosure process in social media users, especially millennials.